(untitled) (Bangladesh Journal of Botany, 2023)
The study was carried out to develop an efficient, reproducible method to overcome the drought stress and increasing agriculture field crisis of Bangladesh. Banglaponics, a soilless cultivation technique comprised of traditional agricultural fertilizers in pond water mixed with cow urine has been used to evaluate the efficiency of tomato production. The production rate (237.85 ± 10.87 g/plant) was significantly (p < 0.05) higher in the Banglaponics medium than soil medium. Plant height, leaf number, leaf area, root number, root length, and flower number of the studied plant showed significantly (p < 0.05) higher in Banglaponics medium than plants grown in soil. Both treatments showed that chlorophyll score and antioxidant activity (DPPH) were almost equal. Banglaponically grown plant leaf, despite having lower Ca concentrations, possessed higher concentrations of Fe and Zn than those of soil-grown. Additionally, Banglaponically grown plant also showed significantly much lower Pb concentrations than that of grown in soil. On the contrary the other two heavy metals Cr and Cd, hold nearly the same value. By appearance, Banglaponically-grown plants were much healthier than that of soil-grown. This technique can be introduced in drought-prone areas of Bangladesh as it requires much less water than soil-grown tomato plants. Bangladesh J. Bot. 52(4): 933-939, 2023 (December)